Temperature and salinity effects on whole-organism and cellular level stress responses of the sub-Antarctic notothenioid fish Patagonotothen cornucola yolk-sac larvae - Bruno, Daniel Osvaldo; Barrantes, María Eugenia; Lattuca, María Eugenia; Nardi, Cristina Fernanda; Diaz, Marina Vera; Wolinski, Laura Isabel; Sacristán, Hernán Javier; Vanella, Fabián Alberto; Fernandez, Daniel Alfredo (Fish Physiology and Biochemistry)
This work aimed to evaluate the whole-organism and cellular level responses to different combinations of water temperature and salinity of the notothenioid Patagonotothen cornucola at the end of the yolk-sac larval stage. Egg masses of the species were collected in the wild and then maintained at natural water conditions (4 °C and 30 PSU). Newly hatched larvae were placed in aquaria with different combinations of water temperature (4 °C, 12 °C, and 16 °C) and salinity (15 and 30 PSU) during four days before yolk sac absorption. Larvae exposed to 12 °C grew more in length than those exposed to 16 °C, but yolk volume was more reduced in larvae exposed to 16 °C than those exposed to 4 °C and 30 PSU than of 15 PSU. In addition, a higher proportion of larvae exposed to 12 °C and 15 PSU completely absorbed their yolk. Whereas the more tolerant larvae to high temperatures were those exposed to 16 °C and 30 PSU, lipid peroxidation and protein oxidation were highest at natural and at 12 °C and 30 PSU conditions, respectively. The nutritional status (as standardized DNA/RNA index—sRD -) was low in all cases, even at natural conditions (average sRD ~ 1). Our study suggests that, in the context of climate change, the mortality rate of yolk-sac larvae of P. cornucola would not increase due to temperature or salinity stress. However, indirect effects (such as habitat degradation or changes in food availability) would be critical after complete absorption of the yolk. Fil: Bruno, Daniel Osvaldo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Barrantes, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Lattuca, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de ...